Entangled reduced graphene oxide nanosheets as an insertion anode with large interlayer spacing for high rate Na-ion batteries. Issue 17 (1st December 2020) - Ali, Ghulam; Mehmood, Asad; Islam, Mobinul; Akbar, Muhammad; Kim, Hyung-Seok; Jung, Hun-Gi; Nam, Kyung-Wan; Chung, Kyung Yoon
Abstract: High performance electrode materials are urgently needed for the commercialization of sodium-ion batteries (SIBs). In the current study, reduced graphene oxide (rGO) is investigated as a high-performance SIB anode material showing high capacity and stability. The rGO with its round sponge morphology has a large interlayer spacing that is highly desirable for enhanced sodium storage capacities. The rGO anode delivers an initial capacity of 330 mAh g −1 at a rate of 50 mA g −1 and delivers an initial capacity of 50 mAh g −1 at a very high rate of 3200 mA g −1 . The reaction mechanism is elucidated using X-ray diffraction combined with transmission electron microscopy, and the results show that the high capacity of the rGO anode is due to the expansion of the interlayer spacing from 0.425 nm to 0.505 nm upon the sodiation process. Furthermore, our prepared rGO anode is tested in the full sodium-ion cell with NaFePO4 as the cathode, and the cell delivers a capacity of 90 mAh g −1, indicating the suitability of the rGO anode for the realization of the economical and high-power performance potential of SIBs.